Integration of Learning Models in Curriculum Development: A Theoretical and Practical Review - Benyamin Metekhohy; Novita Loma Sahertian (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
The curriculum is a major component of the education system that determines the direction and quality of the teaching and learning process at various educational levels. This study aims to analyze the stages of curriculum development in Christian education and to identify its relevance and challenges in the current social and cultural context. The research adopts a qualitative descriptive method, utilizing literature review and document analysis to explore theoretical frameworks, best practices, and contextual applications. The findings indicate that effective curriculum development in Christian education involves three main stages: formulating content aligned with the vision and mission of Christian education, designing learning activities that foster students’ active participation and spiritual growth, and determining evaluation methods that comprehensively measure the achievement of learning objectives. Results also show that integrating Christian faith values with learning materials enhances contextual relevance and holistic student development, although challenges remain in adapting to the rapidly changing social and cultural environment. This study underscores the need for continuous curriculum review and adaptation to ensure that Christian education remains transformative and impactful.